Kesadaran Hukum Masyarakat Kelurahan Budiman Terhadap Tindakan Penyebaran Berita Hoax di Media Sosial - Annisa, Feni; Candra, Alif Aditya; Dewi, Nurmalia (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2025)
This article examines the level of legal awareness among residents of Budiman Village, Jambi City, regarding the dissemination of hoax news on social media. Employing a descriptive qualitative method, data were collected through observations, interviews, and documentation. The analysis process involved data collection, reduction, presentation, and verification. The findings reveal that public legal awareness in Budiman Village remains generally low and unevenly distributed. Many residents lack understanding of legal regulations prohibiting the spread of misinformation under Indonesia’s Electronic Information and Transactions (ITE) Law. Moreover, awareness of the legal consequences for those who disseminate hoaxes is still limited. While some members of the community express moral support for law enforcement efforts, proactive measures to prevent the spread of hoaxes remain scarce. This situation is attributed to insufficient legal outreach, limited access to accurate information, and a lack of public comprehension about digital legal responsibilities. The study underscores the urgent need for continuous and widespread legal education initiatives to foster a more active, responsible, and law-conscious digital society.